The effect of massage and topical violet oil on the severity of pruritus and dry skin in hemodialysis patients: A randomized controlled trial. (August 2019) - Khorsand, Ali; Salari, Roshanak; Noras, Mohammad Reza; Saki, Azadeh; Jamali, Jamshid; Sharifipour, Farzaneh; Mirmoosavi, Seyed Jamal; Ghazanfari, Seyed Majid
Highlights: Pruritus is one of the common problems which usually occurs in CKD and HD patients. Its exact pathogenesis is unclear. Violet oil is an old plant with anti-pruritic & anti-inflammatory effects, which is extensively used to treat diseases in the TIM. This study aimed to evaluate the effect of massaging the body with & without violet oil in the treatment of UP. This paper is a randomized clinical study conducted in Mashhad University of Medical Sciences from 2017 to 2018 with 57 participants of HD patients. The results of this study indicated that massage with violet oil is more effective than massage alone. Abstract: Background: Pruritus is one of the common problems in hemodialysis patients that involves more than 45% of Iranian patients. Its exact pathogenesis is unclear. Meanwhile, violet is an old plant with anti-scratching effects, which is extensively used to treat diseases in the Persian medicine. This study aimed to evaluate the effect of massaging the body with and without violet oil in the treatment of uremic pruritus. Methods: In this study 57 hemodialysis patients who had uremic pruritus were categorized randomly into two groups. The treatment involved massage with and without topical 5 ml violet oil for 7 min during six sessions (two weeks) on the healthy hand which did not have fistula pruritus score questionnaire were completed before and after the intervention. Results: There was no difference between the two groups before the intervention; however, after the intervention, a significant difference was observed within each group and between the groups in terms of skin dryness score, severity, location, and frequency of pruritus, which were recovered significantly in both groups. Conclusion: The results of this study indicated that massage with violet oil is more effective than massage alone and is recommended as a complementary treatment for patients with uremic pruritis.